2018
DOI: 10.1186/s12957-018-1446-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for PNET liver metastases: a systematic review

Abstract: BackgroundPancreatic neuroendocrine tumors (PNETs) are rare pancreatic neoplasms. About 40–80% of patients with PNET are metastatic at presentation, usually involving the liver (40–93%). Liver metastasis represents the most significant prognostic factor. The aim of this study is to present an up-to-date review of treatment options for patients with liver metastases from PNETs.MethodsA systematic literature search was performed using the PubMed database to identify all pertinent studies published up to May 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 107 publications
0
45
0
4
Order By: Relevance
“…To our knowledge, this study is unique in its evaluation of patients with locally advanced PNETs without distant metastatic disease. Most other publications have focused on either resection of liver or distant metastases to determine whether resection improves survival for those patients 8 , 9 , 10 , 11 , 12 , 13 , 14 or on the resection of tumors less than 2 cm (T1/T2 tumors), 20 but this study focused on large, locally advanced tumors. In patients with locally advanced disease, aggressive surgical excision of tumor remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study is unique in its evaluation of patients with locally advanced PNETs without distant metastatic disease. Most other publications have focused on either resection of liver or distant metastases to determine whether resection improves survival for those patients 8 , 9 , 10 , 11 , 12 , 13 , 14 or on the resection of tumors less than 2 cm (T1/T2 tumors), 20 but this study focused on large, locally advanced tumors. In patients with locally advanced disease, aggressive surgical excision of tumor remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of surgery for liver metastases from PNETs has been extensively studied previously. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 However, little is known about surgery for locally advanced PNETs without liver (or other distant) metastases 16 because it has not, to our knowledge, been previously addressed, likely secondary to the rarity of this presentation. It is important because major surgery to resect locally advanced, possibly nodal metastatic PNETs may be morbid and have life-threatening complications.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic therapeutic decisions for the management of PNETs must be personalized and rely on various considerations including functional imaging and molecular profiling in addition to clinical considerations such as hormonal secretion, tumor grade, disease burden, and the rate at which tumor progresses[ 29 ]. These considerations predict whether systemic or locoregional treatment will benefit patients[ 30 ]. The impact of therapies on the quality of the life of the patient must be considered prior to making any therapeutic decision.…”
Section: Current Therapeutic Optionsmentioning
confidence: 99%
“…While 40%-80% of patients with PNET are metastatic at presentation, usually involving the liver (40%-93%) [3], treatment options do exist and include locoregional therapy, chemotherapy, as well as liver transplant [4]. A detailed review on the metastasis of PNET can be found in [5]. Herein, we will focus on the metastasis of PDA.…”
Section: Epidemiology and Clinical Outcome Of Pdamentioning
confidence: 99%